Romanian Legislation Based on The EU Green Deal Strategy - Cristina-Matilda VĂNOAGĂ (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
The present paper presents some of the latest Romanian legal provisions to support the European Green Deal objectives and the adoption of the "Fit for 55" package. Our paper presents some of the latest Romanian legislative initiatives and programs as part of the joint European effort to make Europe the first green continent. Thus, we briefly discuss The National Integrated Energy and Climate Change Plan 2021- 2030, Emergency Ordinance 71/2021 on the promotion of non-polluting road transport vehicles, in support of low-emission mobility, Rabla Plus Program 2024, Emergency Ordinance 108/2022 regarding the decarbonisation of the energy sector, the proposed National Hydrogen Strategy and presents the modifications to the Law 220/ 2008.